Genetic contribution of the HLA region to the familial clustering of coeliac disease - Fiorella Petronzelli; Margherita Bonamico; Paola Ferrante; R. Grillo; Barbara Mora; P. Mariani; Ilaria Apollonio; G. Gemme; M. C. Mazzilli (1997)
In order to assess the effect of the HLA region on familiality of coeliac disease (CD), we carried out a study on 121 CD index cases and 325 first degree relatives. The transmission disequilibrium test confirmed the importance of the HLA-DR3 haplotype in CD susceptibility. However, the different distortion found in affected children inheriting maternal or paternal DR3 alleles suggested that the sex of the parent might influence the risk conferred by this haplotype. The increase in risk to siblings of affected individuals relative to the risk in the general population (lambda s) and the contribution of the HLA genes to this clustering (lambda sHLA) have also been estimated. Non-overlapping data from the literature have been collected and combined with our sample to extend such analysis. Then, the percentage contribution of the HLA region to the development of CD among siblings was 36.2%. This result confirms that the HLA genotypes are an important genetic background to CD development but shows that additional susceptibility factors remain to be identified.